Oddioside A, a New Phenolic Glycoside Isolated from the Fruits of Morus alba (Mulberry), Protects TNF-α-Induced Human Dermal Fibroblast Damage - Kang Sub Kim; Ranhee Kim; So-Ri Son; Ki Sung Kang; Dae Sik Jang; Sullim Lee (MDPI AG, 2022)
In our preliminary study, a hot water extract from the fruits of Morus alba (mulberry) inhibited the secretion of metalloproteinase-1 (MMP-1) against tumor necrosis factor-α (TNF-α)-stimulated human dermal fibroblasts (HDFs), and therefore we researched its active compounds. In the present study, a new phenolic glycoside (oddioside A, 1) and 21 known compounds (2−22) were isolated from the hot water extract from the fruits of M. alba by repeated chromatography. The chemical structure of the new compound 1 was elucidated by its spectroscopic data (1D− and 2D−NMR and HRMS) measurement and by acidic hydrolysis. The presence of sargentodoside E (2), eugenyl glucoside (6), 2-O-β-d-glucopyranosyl-4,6-dihydroxybenzaldehyde (7), 7S,8R-erythro-7,9,9'-trihydroxy-3,3'-dimethoxy-8-O-4'-neolignan-4-O-β-d-glucopyranoside (11), pinoresinol-4-O-β-d-glucopyranoside (12), taxifolin-7-O-β-d-glucopyranoside (20), and pinellic acid (21) were reported from M. alba for the first time in this study. The new compound oddioside A (1) suppressed the secretion of MMP-1 and increased collagen in TNF-α-stimulated HDFs. In addition, the phosphorylation of mitogen-activated protein kinases (MAPKs) was inhibited by oddioside A. In conclusion, the extract from fruits of M. alba and its constituent oddioside A may be a potential agent to prevent inflammation-related skin aging and other skin disorders.